(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Although the Uzbek, Russian and English languages have different genetic bases, their punctuation system relies on a single logical-grammatical basis. From this point of view, in the punctuation of these languages, together with generalizing features, ideological-ethnic specificities characteristic of the last stages of their particular evolution are observed. Russian punctuation played an important role in the formation of the general theoretical foundations of Uzbek punctuation, while the influence of English punctuation on its further development is increasing.